Políticas e práticas de gestão de pessoas e intenção de rotatividade: um estudo com servidores técnico-administrativos em educação do Instituto Federal do Pará na cidade de Belém - GUERRA, Maria Helena Tavares da Silva (Universidade Federal do Pará, 2019)
The present dissertation analyzed the relationship between Human Resource Management (HRM) Policies and Turnover Intention of the Technical-Administrative Servants in Education from Federal Institute of Education, Science and Technology of Pará (IFPA), in exercise in the city of Belém/PA. In this sense, the present research emphasizes the thematic of the retention of public servants, the actors responsible for the materialization of the public policies and attendance of the social demands. In this way, a field research was carried out, through a survey, in which psychometric scales were used to evaluate the perception of the servants in relation to HRM policies and their turnover intentions, characterizing a quantitative study, with the application of descriptive statistical and multiple linear regression techniques. The descriptive results allowed us to observe that the servants do not perceive IFPA's HRM policies and, largely, have medium/high turnover intentions. Through the regression analysis, the hypothesis drawn in this study was partially confirmed, since only the engagement policy was identified as a predictor of the turnover intention in the sample investigated. Finally, a series of recommendations were made in order to contribute to the development and strengthening of HRM within IFPA